The influence of perceived social media marketing activities on brand loyalty: The mediation effect of brand and value consciousness - Rageh, Ahmed (Emerald Group Publishing, 2017)
Â© 2017, Â© Emerald Publishing Limited. Purpose: The purpose of this paper is to investigate the impact of social media marketing activities on brand loyalty, value consciousness and brand consciousness. Design/methodology/approach: A self-administered questionnaire was developed and administered to a convenience sample of 346 undergraduate students Findings: The findings of this research indicated that social media marketing has a significant effect on brand loyalty; brand consciousness and value consciousness mediate the relationship between social media marketing and brand loyalty. Originality/value: This study confirms the growing importance of social media marketing. It also provides insights for marketers on envisioning brand loyalty.